Coenzyme Q10 in the Follicular Fluid and Its Relation to Oocyte Maturity, Fertilization Rate, Embryo Grading, and Pregnancy Rate - Alaa Abdulateef Mohammed1 , Zainab Hassan Al-Khafajy. 2 Ass. Prof Dr. Wasan Adnan Abdullhameed3 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Infertility was define as; a disease characterized by the failure to establish a clinical pregnancyafter 12 months of regular unprotected sexual intercourse, or due to an impairment of a person’s capacityto reproduce, either as an individual or with his/her partner. According to the latest definition by theinternational glossary on infertility and fertility care, regular sexual intercourse is an important determinantfor the occurrence of pregnancy.Aim of the study: To assess the relation between Coenzyme Q10 level in the follicular fluid with oocytematurity, fertilization rate, embryo grading, and pregnancy ratePatients and method: A prospective cross sectional study conducted at the High Institute for InfertilityDiagnosis and Assisted Reproductive Technologies / Al-Nahrain University and in fertility center at AlSadr general hospital during the period from December 2019 to August 2020. Sixty infertile couples wereenrolled in this study; all underwent ICSI cyclesResults: Mean level of Co Q10 in Grade III and IV (0.387 ± 0.54) than that in Grade I and II (0.539 ± 0.65),CoQ10 total in pregnant were 0.79 ± 0.63 and in non-pregnant were 0.381 ± 0.2, A threshold of 0.27 ofCoQ10 had a sensitivity of 80.0% and specificity of 67.0 %, PPV was (88.0%), NPV (45%) and accuracywas (74%). ROC curve of CoQ10 for pregnancy predictionConclusion: Significant decrease of Co Q10 between in Grade III and IV than that in Grade I and II. CoQ10total were increase in pregnant women than non-pregnant.